Meiotic recombination is confirmed to be unusually high in the fission yeast Schizosaccharomyces pombe - Qichao Lian; Laetitia Maestroni; Maxime Gaudin; Bertrand Llorente; Raphael Mercier (iScience, 2023)
Summary: In most eukaryotes, meiotic crossovers (COs) are limited to 1–3 per chromosome, and are prevented from occurring close to one another by CO interference. The fission yeast Schizosaccharomyces pombe, an exception to these general rules, was reported to have the highest CO number per chromosome and no or weak interference. However, global CO frequency was indirectly estimated, calling for confirmation. Here, we used an innovative strategy to determine COs genome-wide in S. pombe. We confirmed weak CO interference, acting at physical distances compatible with the patterning of recombination precursors. We revealed a slight co-variation in CO number between chromosomes, suggesting that a limiting pro-CO factor varies between meiocytes. CO number per chromosome varies proportionally with chromosome size, with the three chromosomes having, on average, 15.9, 12.5, and 7.0 COs, respectively. This reinforces S. pombe’s status as the eukaryote with the highest CO number per chromosome described to date.